Masculine Power Europe? A Discursive Institutionalist Analysis of the European Union’s ‘Strategic Autonomy’ in Security and Defence Policy Through a Gender Perspective - Emersic,Aljaz (2024)
In the context of Russian invasion of Ukraine in February 2022, strategic autonomy (EU-SA) debates in the European Union have gained new saliency, especially in policy area of security and defence. EU-SA in the Common Security and Defence Policy (CSDP) revolves around the issue of EU assuming greater responsibility for its security and defence. The shift towards becoming strategically autonomous thereby speak to the process of EU’s identity reconstruction as a global security and defence actor. Rather than a power traditionally defined by values and ability to diffuse them, EU-SA points to a more pronounced military actorhood. Drawing on theoretical insights of feminist security studies, the thesis draws attention to gender equality as a guiding principle of EU’s external relations and an important claim to its normative power. Inspired by post-structuralist discourse analysis it analyses EU-SA in CSDP as a discourse and links institutional and discursive feminist approaches to the study of EU security within Discursive Institutionalism. The thesis accordingly addresses key questions regarding EU-SA in CSDP: why is it pursued, what it entails and how it can be achieved, and analyses the gendered meanings of identity (re)constructions. Proposing a novel framework for analysing security discourse, the thesis argues that EU-SA in CSDP discourse frames a masculinised crisis narrative marked by threatening masculine Others, which legitimise a desired masculine future identity of the EU as a global security and defence actor with a pronounced military masculinity. This construction ultimately impedes on the EU’s normative stance of promoting gender equality.
Keywords: EU Strategic Autonomy; Common Security and Defence Policy; Feminist Security Studies; Discursive Institutionalism; Gender